Technical and Economic Analysis of Ship Launching with Slipway and Airbag KM. Sabuk Nusantara 72 in PT. Janata Marina Indah Shipyard Semarang - Sunarso Sugeng; Mohammad Ridwan; Suharto Suharto; Samuel Febriary Khristyson (TEKNIK, 2020)
In a ship planning can not be separated from the planning of the ship launching process. A ship can glide perfectly if it has a high enough planning time and costs. The launch process itself is divided into several ways. The choice of this method needs to be considered because it relates to the budget and preparations made. The method used is the calculation according to the numerical approach assisted by computational software. In the first calculation it is planned with the slipway launch, and then the next one is planned with the airbags that have been implemented previously. The purpose of this study is to provide analysis results as a consideration in implementing the slipway and airbag ship launching method on KM ships. Belt Nusantara 72 measuring 2000 DWT. In steps 5 to 6, both the slipway and the airbags experience a stern lift condition with a value (yVd) of 1396.97 ton.  Based on the economic analysis of the hours of people using airbags, there is a decrease in working hours by 44% when compared to the launch using a slipway. This also happened to work productivity where it was 84% more time effective. When viewed from an investment point of view, the use of slipways is actually more economical than airbag, the difference is 43% more economical using slipways. Both types of launch can be applied by looking at the economical side and the ability of each shipyard in carrying out the launching process and seeing the main size of the ship to be launched.